2022
DOI: 10.3390/ijerph19127478
|View full text |Cite
|
Sign up to set email alerts
|

Are Coping Strategies, Emotional Abilities, and Resilience Predictors of Well-Being? Comparison of Linear and Non-Linear Methodologies

Abstract: Emotional intelligence (EI), problem-oriented coping, and resilience have been deeply studied as psychological predictors of wellbeing in stressful daily situations. The aim was to find out whether coping, EI, and resilience are predictors of well-being, using two statistical methodologies (hierarchical regression models and comparative qualitative models). With this objective in mind, we built an online evaluation protocol and administered it to 427 Spanish people, exploring these variables through a selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(57 reference statements)
1
3
0
Order By: Relevance
“…These results are consistent with Sánchez-Álvarez et al [ 39 ] and Xu et al [ 40 ], who also found these variables to be correlated. Resilience had a positive association with SWL, and these results were similar to those of Lacomba-Trejo et al [ 62 ]. Self-esteem was positively associated with SWL.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are consistent with Sánchez-Álvarez et al [ 39 ] and Xu et al [ 40 ], who also found these variables to be correlated. Resilience had a positive association with SWL, and these results were similar to those of Lacomba-Trejo et al [ 62 ]. Self-esteem was positively associated with SWL.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Arslan [ 61 ] found that self-esteem and resilience influenced SWL. Lacomba-Trejo et al [ 62 ] showed that EI and resilience were associated with subjective wellbeing in their cognitive and affective components. As for resilience, it contributed positively to subjective wellbeing [ 63 , 64 , 65 ].…”
Section: Introductionmentioning
confidence: 99%
“…Students' coping strategies and mental resilience examined in the texts analyzed are important for adaptation processes since they are related to appropriate responses in stressful situations, reduce inappropriate emotional reactions, promote positive mood and increase life satisfaction (Lacomba-Trejo et al, 2022). Playfulness has only recently been studied in the context of adults.…”
Section: Discussionmentioning
confidence: 99%
“…16 Finally, being resilient includes effective coping, which is highly individualized. 8,17 Spirituality and religion, social support, self-care (exercise and healthy diet), reflection, and problem-solving are some of the most commonly cited coping strategies nurses employ. 18,19 Although coping strategies differ among nurses, these strategies all serve to support one's resilience.…”
Section: Pediatric Nurse Resilience To Stressorsmentioning
confidence: 99%